Still time to care: what we can learn from the Church's failed attempt to cure homosexuality - Johnson, Greg (Zondervan Reflective, 2021)
"Still Time to Care tells the untold story of the "ex-gay" movement in the evangelical church, a 40-year failed experiment to cure homosexuality. It also provides a four-part postmortem and a path forward--a call to the Christian church to embrace their non-straight fellow believers who live lives of costly obedience"--